PENGARUH KEMAMPUAN MANAJERIAL KEPALA SEKOLAH TERHADAP KINERJA GURU DI MTS DARUNNAJAH 2 CIPINING - Rahma Fajriani; Arizqi Ihsan Pratama; Khairrina; Ahmad Farid (JURNAL ILMIAH RESEARCH STUDENT, 2023)
Managerial ability is closely related to effective leadership management, because in fact management is essentially a matter of interaction between humans both vertically and horizontally, therefore leadership can be said to be a behavior that motivates others to work towards achieving goals and leadership management is very influential on its performance. The purpose of this study was to describe the teacher's performance at MTs Darunnajah 2 Cipining Bogor, to describe the managerial ability of the principal at MTs Darunnajah 2 Cipining Bogor, and to determine whether there was an influence of the principal's managerial ability on teacher performance at MTs Darunnajah 2 Cipining Bogor. The research method used is a quantitative approach. A sampling of 30 teachers. The data collection technique is using a questionnaire. The data analysis technique used is correlation coefficient and multiple regression. It is known that the results of statistical calculations using SPSS 22 show that there is an influence between the managerial ability of the principal (X) and the teacher's performance (Y) at MTs Darunnajah 2 Cipining Bogor. This is evidenced by the results of the calculation of the equation Y = 69.434 + 0.606 X the equation is known as> 0 which means Ho is rejected and Ha is accepted. The results of the coefficient of the determination indicate that the managerial ability of the principal has an influence of 34.5% on the performance of teachers at MTs Darunnajah 2 Cipining Bogor. Keywords: Principal Managerial, Teacher Performance.